Complex Processing of Adsorbent Used in the Purification of Hydrogen-Containing Gas - Sukhrob Ibodullaev; Nurkhon Isaeva; Rustam Khodjiev; Elena Mirzaeva; Dilnoza Turdieva; Shukhrat Gulomov; Shavkat Mamatkulov (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
The problems of processing spent adsorbents with a high concentration of chemisorbed chlorine-containing compounds for their reuse are studied in this article. The genesis of the phase composition and morphology at all technological stages of thermochemical regeneration of the spent adsorbent - Axstrap-860 by means of alkaline modification with a combined solution of sodium and potassium hydroxides has been tested by diffractometry and elemental analysis. The results show that the formation of a layer with an increased concentration of alkali metals in the form of the corresponding carbonates and NaOH on the surface of the granules and in the volume of sodium and potassium aluminates provides adsorption of HCl, which are slightly inferior to the fresh adsorbent. The conditions for the removal of halogen-containing substances from technogenic raw materials with the subsequent isolation of useful products have been optimized: (1) crystalline NaCl intended for the preparation of electrolyte for electrode boilers and steam generators; (2) a mixture of chlorides and hydroxochlorides of aluminum tested in the process of coagulation purification of turbid natural and waste waters; (3) pseudoboehmite for the production of an adsorbent-desiccant and the synthesis of magnesium-aluminum spinel using the technology of destruction-epitaxial transformation, and a promising carrier for catalysts for steam reforming of hydrocarbons. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).